Mainstreaming Madrasah Quality Through Transformation of Regular Classes into CIBI (Islamic-Based Intellectual Intelligence) Classes at MI Ummusshabri Kendari (Pengarusutamaan Mutu Madrasah Melalui Transformasi Kelas Reguler Menjadi Kelas CIBI (Cerdas Intelektual Berbasis Islami) di MI Ummusshabri Kendari) - Supriyanto, Supriyanto; Pairin, Pairin (Shautut Tarbiyah, 2024)
Improving the quality of education in madrasahs is an important focus in facing the challenges of globalization and modernization. MI Ummusshabri Kendari has implemented innovation through the transformation of regular classes into Islamic-Based Intellectual Intelligence (CIBI) classes. This study aims to evaluate the effectiveness of this transformation in improving the quality of learning and student output. The research method used is descriptive research with a qualitative approach. Data were obtained through observation, interviews, and documentation. The results of the study indicate that the transformation of CIBI classes at MI Ummusshabri Kendari has a positive impact on improving the quality of education, both in terms of academics and student character.Keywords:     Quality of education, madrasah, class transformation, Islamic-Based Intellectual Intelligence (CIBI)